Analysis of Pilgrims in Deciding to Register for Umrah on AET Travel - Khairil Azmi; Muhammad Jamil; Faeza Rezi (Penerbit Hellow Pustaka, 2024)
The role of the Umrah and Hajj Travel Bureau is very important for those carrying out the Hajj and Umrah pilgrimages, considering the very high value of the pilgrimage, and its implementation outside Indonesia. Demands for comfort in carrying out the Hajj and Umrah pilgrimages are left entirely to the Special Umrah and Hajj Travel Bureau. Regarding the high cost of the Hajj and Umrah pilgrimages, of course users of Umrah and Hajj Travel Bureau services will be very disappointed if the services provided do not meet the congregation's expectations, thereby reducing the congregation's comfort in worship. The aim of the research is to analyze the behavior of pilgrims in deciding whether to register for Umrah or Hajj at a Hajj and Umrah travel agency. This research uses qualitative methods and is classified as field research with semi-structured interviews and documentation as data collection techniques. The findings from this research are that there are several things that influence pilgrims to make their choice to register for Umrah or Hajj with a Hajj and Umrah travel agency, such as certainty of departure, comfort in service, adequate accommodation and so on.